Are Teachers Crucial for Academic Achievement? Finland Educational Success in a Comparative Perspective - Andere, Eduardo (Education Policy Analysis Archives, 2015)
Teachers are seen as the main reason behind the high, equal, and consistent student performance in Finland as measured by the Programme for International Student Assessment (PISA), and there is a lot of truth in this. Candidates for teacher training programs are selected through a rigorous process, for example. However, using primarily the case of Finland, this paper seeks to show that factors beyond the quality of teachers are also involved in explaining high performance on international standardized tests by students around the world. The policy of attracting high-caliber students and providing high-quality preservice training, suggested by organizations such as the Organisation for Economic Cooperation and Development (OECD) and McKinsey & Company, does not necessarily seem to be related to high student performance in all countries.